Primary Metabolite Responses to Oxidative Stress in Early-Senescing and Paraquat Resistant Arabidopsis thaliana rcd1 (Radical-Induced Cell Death1) - Sipari, Nina; Lihavainen, Jenna; Shapiguzov, Alexey; Kangasjärvi, Jaakko; Keinänen, Markku (Frontiers in Plant Science, 2020)
Rcd1 (radical-induced cell death1) is an Arabidopsis thaliana mutant, which exhibits high tolerance to paraquat (methyl viologen, MV), herbicide that interrupts photosynthetic electron transport chain causing the formation of superoxide and inhibiting NADPH production in the chloroplast. To understand the biochemical mechanisms of MV-resistance and the role of RCD1 in oxidative stress responses, we performed metabolite profiling of wild type (Col-0) and rcd1 plants in light, after MV exposure and after prolonged darkness. The function of RCD1 has been extensively studied at transcriptomic and biochemical level, but comprehensive metabolite profiling of rcd1 mutant has not been conducted until now. The mutant plants exhibited very different metabolic features from the wild type under light conditions implying enhanced glycolytic activity, altered nitrogen and nucleotide metabolism. In light conditions, superoxide production was elevated in rcd1, but no metabolic markers of oxidative stress were detected. Elevated senescence-associated metabolite marker levels in rcd1 at early developmental stage were in line with its early-senescing phenotype and possible mitochondrial dysfunction. After MV exposure, a marked decline in the levels of glycolytic and TCA cycle intermediates in Col-0 suggested severe plastidic oxidative stress and inhibition of photosynthesis and respiration, whereas in rcd1 the results indicated sustained photosynthesis and respiration and induction of energy salvaging pathways. The accumulation of oxidative stress markers in both plant lines indicated that MV-resistance in rcd1 derived from the altered regulation of cellular metabolism and not from the restricted delivery of MV into the cells or chloroplasts. Considering the evidence from metabolomic, transcriptomic and biochemical studies, we propose that RCD1 has a negative effect on reductive metabolism and rerouting of the energy production pathways. Thus, the altered, highly active reductive metabolism, energy salvaging pathways and redox transfer between cellular compartments in rcd1 could be sufficient to avoid the negative effects of MV-induced toxicity.